The activity of Chikurachki volcano (Paramushir Isl., Northern Kuriles) in January–February of 2022 - Artem V. Degterev; Marina V. Chibisova (Геосистемы переходных зон, 2022)
The article considers a short-term moderate explosive eruption of Chikurachki volcano (Paramushir Isl.) on the basis of satellite data. In the period from January 30 to February 3, 2022, at least 8 steam-gas and ash emissions to a height of 2.5–5 km a.s.l. were recorded. Ash plumes and clouds spread mainly in the south-western, western, southern, and south-eastern directions at a distance up to 250 km from the volcano. Its parameters were similar to the previous explosive eruptions of Chikurachki volcano. Due to high frequency of moderate explosive eruptions of Chikurachki volcano in recent years, when ash clouds rise to a height up to 7.5 km a.s.l. and ash plumes are formed that can spread for several hundred kilometers, the volcano poses a potential hazard to international and local airlines.